Sleep Duration and the Risk of Metabolic Syndrome in Adults: A Systematic Review and Meta-Analysis - Hua, Jianian; Jiang, Hezi; Wang, Hui; Fang, Qi (Frontiers in Neurology, 2021)
Abstract Objective: Epidemiological studies have reported inconsistent findings for the association between sleep duration and metabolic syndrome. We aimed to clarify the effects of short and long sleep durations on metabolic syndrome in adults by performing a meta-analysis. Methods: Adopting random-effects models, this study analyzed the effects of short and long sleep durations based on data from prospective cohort studies and cross-sectional studies retrieved from four electronic databases from inception to May 2020. Results: We collected data from 235,895 participants included in 9 prospective cohort studies and 340,492 participants included in 27 cross-sectional studies. In cohort studies, a short sleep duration was associated with an increased risk of metabolic syndrome (RR, 1.15; 95% CI, 1.05-1.25, I2=63.1%, P<0.001) compared with a normal sleep duration. While a long sleep duration was not associated with new onset metabolic syndrome (RR, 1.02, 0.85-1.18, I2=38.0%, P=0.491). In cross-sectional studies, both short (OR, 1.06, 95% CI, 1.01-1.11, I2=66.5%, P<0.001) and long (OR, 1.11, 95% CI, 1.04-1.17, I2=73.8%, P<0.001) sleep durations were associated with a high prevalence of metabolic syndrome. Conclusions: Only a short sleep duration was associated with an increased risk of metabolic syndrome. Future studies should address whether the association is casual and modifiable.